Investigation of shell and tube heat exchangers by using a design of experiment - S. Balamurugan; D.P. Samsoloman (Journal of Heat and Mass Transfer Research, 2014)
Heat exchangers are one of the most important devices of mechanical systems in modernsociety. Most industrial processes involve the transfer of heat and more often they requirethe heat transfer process to be controlled. A heat exchanger is the heat exchanged betweentwo media, one being cold and the other being hot. There are different types of heatexchanger, but the type which is widely used in industrial application is the shell and tube.In this study, experiments conducted based on fully replicable five-factor, five-level centralcomposite design. Regression modelsare developed to analyse the effects of shell and tubeheat exchange process parameter such as inlet temperature of hot fluid and flow rates ofcold and hot fluid. The output parameters of a heat exchanger are used for analysing thedirect and interactive effects of heat exchange process parameters.